2020
DOI: 10.1111/cge.13704
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation sequencing through multi‐gene panel testing for diagnosis of hereditary ichthyosis in Chinese

Abstract: Inherited ichthyoses are a heterogeneous group of rare disorders related to over 40 genes. To identify underlying molecular causes in inherited ichthyosis among Chinese and to correlate genotype and phenotype, 35 probands clinically diagnosed inherited ichthyosis, except ichthyosis vulgaris and X-linked ichthyosis, were included in our study. Molecular analysis was performed using next-generation sequencing (NGS) through multi-gene panel testing targeting all ichthyosis-related genes. Genetic variants causativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…However, according to the literature, 15 -20 % of patients with the ARCI diagnosis do not have pathogenic variants in any of the known genes. In 2016, Shigehara et al found pathogenic homozygous missense variants in SDR9C7 with lamellar ichthyosis in three consanguineous Lebanese families (Shigehara et al, 2016), and more recent reports of pathogenic variants in SDR9C7 in ARCI patients from Japan, Austria, Pakistan, France and China provide additional evidence on the role of this gene in pathogenesis of non-syndromic ichthyosis (Takeichi et al, 2017;Seidl-Philipp et al, 2019;Karim et al, 2017;Hotz et al, 2018; J o u r n a l P r e -p r o o f Mazereeuw-Hautier et al, 2020;Cheng et al, 2020;Simpson et al, 2020). However, these studies failed to identify genotype-phenotype correlations.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the literature, 15 -20 % of patients with the ARCI diagnosis do not have pathogenic variants in any of the known genes. In 2016, Shigehara et al found pathogenic homozygous missense variants in SDR9C7 with lamellar ichthyosis in three consanguineous Lebanese families (Shigehara et al, 2016), and more recent reports of pathogenic variants in SDR9C7 in ARCI patients from Japan, Austria, Pakistan, France and China provide additional evidence on the role of this gene in pathogenesis of non-syndromic ichthyosis (Takeichi et al, 2017;Seidl-Philipp et al, 2019;Karim et al, 2017;Hotz et al, 2018; J o u r n a l P r e -p r o o f Mazereeuw-Hautier et al, 2020;Cheng et al, 2020;Simpson et al, 2020). However, these studies failed to identify genotype-phenotype correlations.…”
Section: Introductionmentioning
confidence: 99%
“…The mutation found in this patient enriched our understanding of pathogenic mutations for CDS. As it is not easy to obtain an accurate diagnosis only based on the dermal features, a blood smear and mutational analysis are required for patients suspected with congenital ichthyosis ( Cheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has a higher gene mutation detection rate. By applying multigene panel testing methods, the molecular cause has been successfully elucidated in 91% of 35 inherited ichthyosis patients (Cheng et al, 2020) and 90% of 40 suspected epidermolysis bullosa patients (Has et al, 2018). Although it is not a 100% discovery rate, there is undoubtedly an economic and a time advantage to panel genetic testing versus a stepwise approach, which is one of the alternative effective methods to help clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%